A prospective cohort study to evaluate continuous wound infusion with local analgesics within an enhanced recovery protocol after colorectal cancer surgery. (16th June 2022) - Ketelaers, Stijn H. J.; Dhondt, Lieke; van Ham, Nikki; Harms, Ansgar S.; Scholten, Harm J.; Nieuwenhuijzen, Grard A. P.; Rutten, Harm J. T.; Burger, Jacobus W. A.; Bloemen, Johanne G.; Vogelaar, F. Jeroen
Abstract: Aim: To reduce detrimental opioid‐related side effects, minimising the postoperative opioid consumption is needed, especially in older patients. Continuous wound infusion (CWI) with local analgesics appears to be an effective opioid‐sparing alternative. However, the added value of CWI to an enhanced recovery protocol after colorectal cancer (CRC) surgery is unclear. The aim of this study was to evaluate the outcomes of CWI after CRC surgery within a strictly adhered to enhanced recovery protocol. Methods: In this multicentre prospective observational cohort study, patients who underwent CRC surgery between May 2019 and January 2021 were included. Patients were treated with CWI as adjunct to multimodal pain management within an enhanced recovery protocol. Postoperative opioid consumption, pain scores and outcomes regarding functional recovery were evaluated. Results: A cohort of 130 consecutive patients were included, of whom 36.2% were ≥75 years. Postoperative opioids were consumed by 80 (61.5%) patients on postoperative day 0, and by 28 (21.5%), 27 (20.8%), and 18 (13.8%) patients on postoperative days 1, 2, and 3, respectively. Median pain scores were <4 on all days. The median time until first passage of stool was 1.0 (IQR: 1.0–2.0) day. Postoperative delirium occurred in 0.8%. Median length of hospital stay was 3.0 days (IQR: 2.0–5.0). Conclusion: In patients treated with CWI, low amounts of postoperative opioid consumption, adequate postoperative pain control, and enhanced recovery were observed. CWI seems a beneficial opioid‐sparing alternative and may further improve the outcomes of an enhanced recovery protocol after CRC surgery, which seems especially valuable for older patients.